Sequence A(n) is defined as follows A(1)=3 A(n)= a(n-2) + : Quant Question Archive [LOCKED]
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 18 Jan 2017, 18:20

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Sequence A(n) is defined as follows A(1)=3 A(n)= a(n-2) +

Author Message
CEO
Joined: 21 Jan 2007
Posts: 2756
Location: New York City
Followers: 11

Kudos [?]: 851 [0], given: 4

Sequence A(n) is defined as follows A(1)=3 A(n)= a(n-2) + [#permalink]

### Show Tags

23 Oct 2007, 08:57
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Sequence A(n) is defined as follows

A(1)=3
A(n)= a(n-2) + A(n-1)

If A(5)= 6, what is A(2)?

-3
-1
0
2
3
Current Student
Joined: 31 Aug 2007
Posts: 369
Followers: 1

Kudos [?]: 127 [0], given: 1

### Show Tags

23 Oct 2007, 09:10
0? I will post if I'm correct...
VP
Joined: 10 Jun 2007
Posts: 1459
Followers: 7

Kudos [?]: 255 [0], given: 0

### Show Tags

23 Oct 2007, 10:48
bmwhype2 wrote:
Sequence A(n) is defined as follows

A(1)=3
A(n)= a(n-2) + A(n-1)

If A(5)= 6, what is A(2)?

-3
-1
0
2
3

A(5) = 6 = A(3) + A(4)
and...
A(3) = A(1) + A(2)
A(4) = A(2) + A(3) = A(2) + A(1) + A(2)
so...
A(5) = A(1) + A(2) + A(2) + A(1) + A(2) = 2*A(1) + 3*A(2)
6 = 2*3 + 3*A(2)
A(2) = 0
Manager
Joined: 25 Apr 2007
Posts: 50
Followers: 1

Kudos [?]: 2 [0], given: 0

### Show Tags

23 Oct 2007, 11:38
bkk145,

neatly done !!!!
CEO
Joined: 21 Jan 2007
Posts: 2756
Location: New York City
Followers: 11

Kudos [?]: 851 [0], given: 4

### Show Tags

24 Oct 2007, 12:29
bkk145 wrote:
bmwhype2 wrote:
Sequence A(n) is defined as follows

A(1)=3
A(n)= a(n-2) + A(n-1)

If A(5)= 6, what is A(2)?

-3
-1
0
2
3

A(5) = 6 = A(3) + A(4)
and...
A(3) = A(1) + A(2)
A(4) = A(2) + A(3) = A(2) + A(1) + A(2)
so...
A(5) = A(1) + A(2) + A(2) + A(1) + A(2) = 2*A(1) + 3*A(2)
6 = 2*3 + 3*A(2)
A(2) = 0

Why do we have to figure that A(2) thru a(5)
why cant we plug in a(2)?
Director
Joined: 11 Jun 2007
Posts: 931
Followers: 1

Kudos [?]: 175 [0], given: 0

### Show Tags

24 Oct 2007, 12:35
bkk145 wrote:
bmwhype2 wrote:
Sequence A(n) is defined as follows

A(1)=3
A(n)= a(n-2) + A(n-1)

If A(5)= 6, what is A(2)?

-3
-1
0
2
3

A(5) = 6 = A(3) + A(4)
and...
A(3) = A(1) + A(2)
A(4) = A(2) + A(3) = A(2) + A(1) + A(2)
so...
A(5) = A(1) + A(2) + A(2) + A(1) + A(2) = 2*A(1) + 3*A(2)
6 = 2*3 + 3*A(2)
A(2) = 0

perfect explanation!
CEO
Joined: 21 Jan 2007
Posts: 2756
Location: New York City
Followers: 11

Kudos [?]: 851 [0], given: 4

### Show Tags

24 Oct 2007, 12:39
bmwhype2 wrote:
bkk145 wrote:
bmwhype2 wrote:
Sequence A(n) is defined as follows

A(1)=3
A(n)= a(n-2) + A(n-1)

If A(5)= 6, what is A(2)?

-3
-1
0
2
3

A(5) = 6 = A(3) + A(4)
and...
A(3) = A(1) + A(2)
A(4) = A(2) + A(3) = A(2) + A(1) + A(2)
so...
A(5) = A(1) + A(2) + A(2) + A(1) + A(2) = 2*A(1) + 3*A(2)
6 = 2*3 + 3*A(2)
A(2) = 0

Why do we have to figure that A(2) thru a(5)
why cant we plug in a(2)?

all right. i figured it out. this sequence equation builds off other functions so we have to keep re-defining until we hit a defined function, in this case A(5) and A(1)
Re: Challenge - Sequence   [#permalink] 24 Oct 2007, 12:39
Display posts from previous: Sort by